The Effects of Using Prehospital Calcium Gluconate During Cardiopulmonary Resuscitation: A Retrospective Study - Huabbangyang, Thongpitak; Silakoon, Agasak; Soimongkolchai, Suchanaree; Dangsawasd, Punyawee; Phankhot, Siravit; Yomklang, Piyada; Sangketchon, Chunlanee (Archives of Academic Emergency Medicine, 2025)
Introduction: Calcium gluconate (CG) administration during cardiopulmonary resuscitation (CPR) has not been recommended in routine clinical practice. This study examined the impact of prehospital CG administration on outcomes of out-of-hospital cardiac arrest (OHCA) cases. Methods: This retrospective cohort study collected data on adult patients aged >18 years who experienced non-traumatic OHCA and were transported by the emergency medical service (EMS) to the emergency department. Data on return of spontaneous circulation (ROSC) at the scene, survival to hospital admission, and survival to hospital discharge were obtained from EMS reports and electronic medical records and compared between OHCA cases who received or didn’t receive CG. Results: In total, 215 adult patients with non-traumatic OHCA were enrolled in this study. Among them, 107 received CG and 108 didn’t receive. In particular, CG administration was associated with a lower rate of ROSC at the scene compared with cases without its administration (8.6% lower). The likelihood of ROSC at the scene was 0.75 times that of those who did not receive CG. CG administration was associated with a lower survival to hospital admission (16.48% lower). The likelihood of survival to hospital admission was 0.42 times that of patients who did not receive CG. In addition, survival to hospital discharge was 7.37% lower in patients who received CG, and the likelihood of survival to hospital discharge was 0.21 times that of those who did not receive CG. Conclusions: Prehospital CG administration by the EMS team did not improve ROSC in the scene, survival to hospital admission, or survival to hospital discharge. The findings highlight the need for selective use of calcium based on guideline-recommended indications rather than empirical administration.